Identifying spatial correlation and factors influencing regional economic growth in Southern Sumatra - Nengsi Puspita Dewi; Tanti Novianti; Dedi Budiman Hakim (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
This study analyzes the spatial autocorrelation of economic growth and labor and the factors that influence economic growth between districts/cities in the Southern Sumatra region. The data used is secondary data sourced from the Bureau of Central Statistics. The method used is a quantitative approach by applying the Moran Index, LISA, and multiple regression models. This study shows that the spatial autocorrelation of economic growth did not occur in the Southern Sumatra region. Meanwhile, the spatial autocorrelation of labor occurs in this region so that it affects each other. This study’s finding that jointly the variables of potential market indicator, fixed capital investment, human capital, and labor force participation rate have a significant effect on GRDP. Likewise, partially the potential market indicators, capital fixed asset investment, human resources, and labor force participation rates have a positive and significant effect on GRDP.